2021
DOI: 10.3390/ijms22084188
|View full text |Cite
|
Sign up to set email alerts
|

RNA Expression of DNA Damage Response Genes in Muscle-Invasive Bladder Cancer: Influence on Outcome and Response to Adjuvant Cisplatin-Based Chemotherapy

Abstract: Background: Perioperative cisplatin-based chemotherapy (CBC) can improve the outcome of patients with muscle-invasive bladder cancer (MIBC), but it is still to be defined which patients benefit. Mutations in DNA damage response genes (DDRG) can predict the response to CBC. The value of DDRG expression as a marker of CBC treatment effect remains unclear. Material and methods: RNA expression of the nine key DDRG (BCL2, BRCA1, BRCA2, ERCC2, ERCC6, FOXM1, RAD50, RAD51, and RAD52) was assessed by qRT-PCR in a cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The expression levels of BRCA1 and RBBP8 were not significantly correlated with the OS of patients with bladder cancer ( Figure 2 ). However, BRCA1 and RBBP8 were correlated with the efficacy of cisplatin-based neoadjuvant chemotherapy, which was more significantly associated with poor disease-free survival ( 11 ). BRCA1 mRNA expression was related to the outcome of neoadjuvant cisplatin-based chemotherapy in bladder cancer; the median survival was 168 months for patients with low expression levels and 34 months for patients with high expression levels ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…The expression levels of BRCA1 and RBBP8 were not significantly correlated with the OS of patients with bladder cancer ( Figure 2 ). However, BRCA1 and RBBP8 were correlated with the efficacy of cisplatin-based neoadjuvant chemotherapy, which was more significantly associated with poor disease-free survival ( 11 ). BRCA1 mRNA expression was related to the outcome of neoadjuvant cisplatin-based chemotherapy in bladder cancer; the median survival was 168 months for patients with low expression levels and 34 months for patients with high expression levels ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al found that the DDR key gene BRCA1 could be inhibited by XPC inhibition in BLCA, which could lead to increased chromosomal instability and maintaining cisplatin-induced DNA damage [ 68 ]. Moreover, DDR-related genes have been found to be able to effectively predict disease-free survival for muscle-invasive BLCA [ 69 ]. The same effect has also been found in Doxorubicin, Mitomycin and Camptothecin, which are mainly dependent on the DNA-cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, mutations in DNA damage response genes (DDRG) can predict the response to cisplatin-based chemotherapy. Herrmann et al [ 10 ] examined the value of RNA expression levels of several key DDRGs ( BCL2 , BRCA1 , BRCA2 , ERCC2 , ERCC6 , FOXM1 , RAD50 , RAD51 , and RAD52 ) in patients with muscle-invasive bladder cancer and validated these with The Cancer Genome Atlas (TCGA). It was determined that the low expression of RAD52 correlated with decreased disease-free survival in patients, which was validated by TCGA.…”
mentioning
confidence: 99%